Financing agribusiness and value chain development in the Pacific - Bovoro, Tukana; Francis, Judith Ann; Neate, Paul J.H. (Technical Centre for Agricultural and Rural Cooperation, 2019)
The agriculture sector, a major source of food and livelihood for up to 80% of the population in Pacific Island Countries, is under-funded. Lending to the sector is less than 2%, despite its contribution to gross domestic product (GDP). Transforming the Pacific agri-food system to address the major socio-economic challenges – malnutrition, high dependence on imported foods, unemployment and climate change – will require targeted public and private investments. Financial institutions and governments must work together to offer innovative financial instruments that enhance access to banking services, especially in the rural areas. Inclusivity is a win-win strategy.